An overview of the diseases constraining the production and productivity in cowpea: With focus in bacterial blight disease caused by Xanthomonas axonopodis pv. vignicola - Kirarei Ezra; Kipsumbai Pixley; Pascaline Jeruto; Kiprop Ezekiel (African Journal of Education,Science and Technology (AJEST), 2025)
Vigna unguiculata L. Walp. L. (cowpea) is a significant legume crop mainly cultivated by small-scale growers in sub-Saharan Africa for human food (vegetables and grains) and animal fodder. The main aim of this review was to examine the production and productivity limitations of cowpea cultivars, with an emphasis on bacterial blight disease. To achieve our objective, we evaluated literature from multiple sources, focusing on relevant information for our review. In sub-Saharan Africa, Kenya is among the leading countries in cowpea production, with Nigeria leading in West Africa, which accounts for approximately 61% of global cowpea output. Cowpeas are affected by a broad range of diseases and pests, resulting to the destruction of entire crops. Continuous crop improvement is essential for the development of new cowpea varieties that do well under varied environmental conditions and are resistant to a wide range of diseases and pests. There is a serious need for interdisciplinary cooperation between breeders and other important actors, such as agricultural extension officers and farmers. There is a pressing demand for cowpea breeding initiatives that concentrate on breeding cultivars with early maturity, disease, pest, and drought tolerance due to sub-Saharan Africa’s diminishing rainfall pattern, increases in pests and diseases, and changing environmental conditions. The current review evaluates the diseases constraining the yield and performance of cowpea, with an emphasis on the bacterial blight of cowpea.